CUSTOMER SPECIFIC COMPATIBILITY MATRICES FOR FUNCTIONAL INTEGRAL PRODUCT ARCHITECTURES. (May 2020) - Siebrecht, J.; Jacobs, G.; Konrad, C.; Wyrwich, C.; Schäfer, W.
Abstract: Supplier of system components face the challenge of customer requirements influencing the property level functional integral product architectures. For this, solution approaches focusing on the re-use of pre-engineered part variants are not applicable. However, to generate a valid product structure, customer-specific properties have to fit modelled product knowledge. Therefore, the approach models a reference class structure and analysis compatibilities on the property level for customer specific inputs concerning explicit product knowledge and constraints.